Utilising quality of life outcome trajectories to aid patient decision making in pelvic exenteration. Issue 11 (November 2022) - Harji, Deena P.; Williams, Anwen; McKigney, Niamh; Boissieras, Lara; Denost, Quentin; Fearnhead, Nicola S.; Jenkins, John T.; Griffiths, Ben
Abstract: Background: Shared decision-making in pelvic exenteration is a complex and detailed process, which must balance clinical, oncological and patient-reported outcomes (PROs), whilst addressing and valuing the patient priorities. Communicating patient-centred information on quality of life (QoL) and functional outcomes is an essential component of this. The aim of this systematic review was to understand the impact of pelvic exenteration on QoL PROs over a longitudinal period and to develop QoL trajectories to support decision-making in this context. Methods: MEDLINE, Embase and Web of Science databases were searched between 1 st January 2000 and 20 th December 2021 Studies reporting on PROs, including QoL, in adults undergoing pelvic exenteration were included. Risk of bias was assessed using the ROBINS-I assessment tool. Data from studies reporting QoL using the same outcome measure at the same candidate timepoint were extracted and synthesised to develop a longitudinal QoL trajectory. Results: Fourteen studies consisting of 1370 patients were included in this review. QoL trajectories were constructed in the domains of physical function, psychological function, role function, sexual function, body image and general and specific symptoms. Decision-making was only assessed by one study, with satisfaction with decision-making reported to be high. There is an initial decline in QoL scores in the domains of physical function, role function, sexual function, body image and general health and symptoms deteriorating during the first 3–6 months post-operatively. Psychological function is the only QoL domain that remains stable throughout the post-operative period. Conclusion: Mapping QoL trajectories provides a visual representation of post-operative progress, highlighting the enduring impact of pelvic exenteration on patients and can be used to inform pre-operative shared decision-making.